2015
DOI: 10.1242/dev.122390
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid signaling regulates development of the dorsal forebrain midline and the choroid plexus in the chick

Abstract: The developing forebrain roof plate (RP) contains a transient signaling center, perturbations in which have been linked to holoprosencephaly (HPE). Here, we describe a novel domain of retinoic acid (RA) signaling that is specific to the chick RP and demonstrate that RA signaling is sufficient for inducing characteristics of the RP in ectopic locations. We further demonstrate that, unlike what has been observed in the mouse, RA signaling is essential for invagination of the RP in chick, failure of which leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…2C, n=5 per group). The latter result is consistent with previous reports of reduced proliferation at the hemisphere midline (Furuta et al, 1997;Gupta and Sen, 2015). Furthermore, the dynamic shift in proliferation is consistent with stage-dependent gene expression in chicken, where the territory of Bmp4 expression remains fairly small until HH18 (Crossley et al, 2001).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2C, n=5 per group). The latter result is consistent with previous reports of reduced proliferation at the hemisphere midline (Furuta et al, 1997;Gupta and Sen, 2015). Furthermore, the dynamic shift in proliferation is consistent with stage-dependent gene expression in chicken, where the territory of Bmp4 expression remains fairly small until HH18 (Crossley et al, 2001).…”
Section: Resultssupporting
confidence: 92%
“…At later stages of hemisphere morphogenesis, mesenchyme between the cortical hemispheres has been proposed as a crucial factor in roof plate signaling and hemisphere maintenance (Choe et al, 2014), potentially exerting force to assist roof plate invagination (Gupta and Sen, 2015). Notably, our model did not require downward force from the dorsal mesenchyme to initiate hemisphere division (Fig.…”
Section: Limitations and Future Workmentioning
confidence: 77%
“…Experimental manipulation of these regions by electroporation of VP16 or dominant-negative RA receptor constructs suggested that Cyp26a1 expression was required to restrict RA-signalling which conferred dorsal forebrain identity and was required for invagination of Rathke's Pouch. Furthermore, degradation of RA by Cyp26a1 in the flanking regions to provide an RA-negative domain was necessary for the development of the choroid plexus [271].…”
Section: Forebrainmentioning
confidence: 99%
“…Expression vectors were: pCAGGS-GFP, pCAGGS-RFP [77], Ptc1 [78], PTC Δloop2 [23,78], a retinoic acid reporter fused to alkaline phosphatase (pRARE-AP, from J. Sen) [79], a dominant negative pan-retinoic acid receptor (RAR403dn-IRES-GFP, from S. Sockanathan) that abrogates retinoic acid signaling [80], full length Shh [23], cholesterol deficient Shh (mShh-N-YFP, from V. Wallace) [33] that was subcloned into pCAGGS, and Hhip1 [23]. To produce Hhip1:CD4, a membrane-tethered version of Hhip1, the transmembrane and intracellular domains of mouse CD4 were fused to the C-terminal domain of Hhip1 lacking amino acids A679-V700, as previously described [31,32] and further subcloned into pCAGGS for electroporation.…”
Section: Expression Vectors and Electroporationmentioning
confidence: 99%